Playfulness in Early Childhood Education: Contributions to the development and learning of children aged 0 to 3 in Municipal Early Childhood Education Centers (CEMEI) in the municipality of Alegre, State of Espírito Santo (ES), Brazil (Research, Society and Development, 2026)
This article aims to analyze the role of play as a pedagogical strategy in the development and learning of children aged 0 to 3 years attending Municipal Early Childhood Education Centers (CEMEIs) in the municipality of Alegre/ES. It complements the articles in a line of research in early childhood education by the authors of this study. It is based on the assumption that play constitutes the language of childhood and a structuring element of educational practices in the first stage of Basic Education. The research is characterized as qualitative, of an empirical nature, carried out through the application of questionnaires, semi-structured interviews with teachers, and observation of pedagogical practices. The theoretical foundation is based on the contributions of Piaget, Vygotsky, Wallon, Kishimoto, Tardif, Nóvoa, and Andrade, articulated with the National Curriculum Guidelines for Early Childhood Education and the National Common Curriculum Base. The results indicate that playful practices favor engagement, autonomy, and the integral development of children; However, they highlight challenges related to teacher training and the structural conditions of the institutions. It is concluded that pedagogical intentionality and continuing education are decisive elements for consolidating play as a structuring axis of learning in early childhood.